2016
DOI: 10.1038/am.2016.53
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding sodium-ion diffusion in layered P2 and P3 oxides via experiments and first-principles calculations: a bridge between crystal structure and electrochemical performance

Abstract: Layered Na x MeO 2 (Me = transition metal) oxides, the most common electrode materials for sodium-ion batteries, fall into different phases according to their stacking sequences. Although the crystalline phase is well known to largely influence the electrochemical performance of these materials, the structure-property relationship is still not fully experimentally and theoretically understood. Herein, a couple consisting of P2-Na 0.62 Ti 0.37 Cr 0.63 O 2 and P3-Na 0.63 Ti 0.37 Cr 0.63 O 2 materials having near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 46 publications
1
88
1
Order By: Relevance
“…In addition, K ions in this P2-type structure can rapidly diffuse between the adjacent prismatic sites by direct hopping through the face-sharing facets. [25,[37][38][39][40] In comparison, for O3-type compounds, alkali ions in the octahedral sites migrate via face-sharing tetrahedral sites, which has a higher activation barrier due to the strong electrostatic repulsion between the alkali ion in the tetrahedral site and metal ion in the MO 6 layers. [39] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, K ions in this P2-type structure can rapidly diffuse between the adjacent prismatic sites by direct hopping through the face-sharing facets. [25,[37][38][39][40] In comparison, for O3-type compounds, alkali ions in the octahedral sites migrate via face-sharing tetrahedral sites, which has a higher activation barrier due to the strong electrostatic repulsion between the alkali ion in the tetrahedral site and metal ion in the MO 6 layers. [39] …”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the P2-type host structure can better maintain its structural stability upon electrochemical cycling compared to other types of compounds, [31,37] leading to better cyclability. In addition, K ions in this P2-type structure can rapidly diffuse between the adjacent prismatic sites by direct hopping through the face-sharing facets.…”
Section: Discussionmentioning
confidence: 99%
“…It can be found that the peak current I p is linearly related to the square root of scanning rate ν 1/2 (Figure 4b), indicating that the kinetics exhibit a behavior similar to diffusion process. The D app calculated from the slope of dI p /dν 1/2 is competitive among many layered metal oxides reported for NIBs [21,24] (Table S2, Supporting Information). The high Na-ion diffusion coefficient is responsible for the competitive rate property of this O3-type cathode material.…”
Section: Excellent Comprehensive Performance Of Na-based Layered Oxidmentioning
confidence: 99%
“…[221] Similarly, Zhou and co-workers also proposed a P2-O3 composite (Figure 12b) with the composition Na 0. 66 Li 0.18 Mn 0. 71 Ni 0.21 Co 0.08 O 2+d .…”
Section: Multiple Metal-based Oxidesmentioning
confidence: 99%
“…Interestingly, layered Ti-substituted Na x Cr x Ti 1−x O 2 was explored as bifunctional electrode materials for SIBs based on Cr 3+ /Cr 4+ and Ti 3+ /Ti 4+ redox couples. [65,66] Yabuuchi and co-workers pointed out that the suppressing the formation of low-crystallinity phases upon Na removal, which might induce irreversible Cr migration into Na layers, is key to improving the reversible capacity of P2-type Na 2/3 Cr 1−x Ti x O 2 cathode material for Na batteries. [67] www.advenergymat.…”
Section: Single-metal-based Oxides Peculiar To Sibsmentioning
confidence: 99%